REFORM PROCESSES REGARDING LIMITED LIABILITY COMPANIES IN LEGISLATION OF EUROPEAN UNION AND ITS MEMBER STATES - Vasiljević, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2023)
Unlike national legislations, at the level of the European Union, more detailed regulation of limited liability companies is lacking. However, in the last twenty years, there has been a trend of facilitating the establishment and business conditions of this type of companies, as the most suitable form for conducting such a process. The author presents and analyzes development and implementation of the idea of mitigating the conditions for the establishment of limited liability companies, especially through the creation of its special form - a simplified limited liability company. It is stated that better results were achieved at the national level, but also that there were progress at the level of the European Union, especially in terms of creating possibility for full electronic registration. It turned out that all efforts in this area have led to an increase in the number of newly established limited liability companies and especially their subtype of simplified companies.